Factors Affecting Survival in Retroperitoneal Sarcomas Treated with Upfront Surgery: A Real-World Study by Turkish Oncology Group - AKIN TELLİ, TUĞBA (AKAD DOKTORLAR YAYINEVI, 2021)
Retroperitoneal sarcomas (RPS) account for approximately 15% of all soft tissue sarcomas (STS) and encompass a heterogeneous group of tumors with limited multimodality treatment options. Surgical resection with negative margins remains the standard primary treatment for patients with localized RPS. In this multicenter study, we aimed to demonstrate the real-world data on factors affecting survival in RPS treated with upfront surgery. We included a total of 197 patients who underwent curative-intent resection of a primary non-metastatic RPS between 2000-2020 at ten experienced medical oncology departments in Turkey. The median follow-up was 33 months. The median age of patients was 53 years, 57.4% of patients were female. Univariate analysis revealed that; tumor size, grade, necrosis, resection margin status, were factors affecting recurrence-free survival (RFS) (p= 0.002, p= 0.044, p= 0,024, p= 0.003 respectively). Age, tumor size, stage, resection margin status were factors affecting overall survival (OS) (p= 0.038, p= 0.001, p= 0.032, p< 0.001, respectively). In multivariate analysis, tumor size and resection margin status were independent factors affecting RFS and OS (all p-values < 0.05). Our study demonstrated that tumor size, and resection margin status were the main factors affecting survival in resected RFS. In comparison, adjuvant chemotherapy (CT), radiotherapy (RT), or multimodality treatment did not show OS and RFS advantages. We believe that advances in the molecular characterization of these tumors might help clinicians to detect the best candidates for adjuvant therapies in RPS.
Keywords: Survival; Retroperitoneal sarcoma; Adjuvant chemotherapy; Adjuvant radiotherapy; Surgery; SOFT-TISSUE SARCOMA; LONG-TERM SURVIVAL; PROGNOSTIC-FACTORS; ADJUVANT CHEMOTHERAPY; MANAGEMENT; RECURRENCE; RESECTION; RADIOTHERAPY